1992
DOI: 10.1080/01431169208904049
|View full text |Cite
|
Sign up to set email alerts
|

High-spectral resolution data for determining leaf water content

Abstract: Background: Cognitive Muscular TherapyTM (CMT) is an integrated behavioural intervention developed for knee osteoarthritis. CMT teaches patients to reconceptualise the condition, integrates muscle biofeedback and aims to reduce muscle overactivity, both in response to pain and during daily activities. This nested qualitative study explored patient and physiotherapist perspectives and experiences of CMT.Methods: Five physiotherapists were trained to follow a well-defined protocol and then delivered CMT to at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
133
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 290 publications
(142 citation statements)
references
References 15 publications
9
133
0
Order By: Relevance
“…It is believed that the variation in leaf structure causes the magnitude of leaf reflectance to change irrespective of the leaf water content. However, the relative "depths" of the water absorption features in the reflectance spectra seem not be affected by leaf structure (Danson et al 1992). As the depth of an absorption feature increases, the slopes on the edges of the feature also increase.…”
Section: Research Articlementioning
confidence: 99%
See 3 more Smart Citations
“…It is believed that the variation in leaf structure causes the magnitude of leaf reflectance to change irrespective of the leaf water content. However, the relative "depths" of the water absorption features in the reflectance spectra seem not be affected by leaf structure (Danson et al 1992). As the depth of an absorption feature increases, the slopes on the edges of the feature also increase.…”
Section: Research Articlementioning
confidence: 99%
“…The linear correlation analysis showed that there exists a statistically significant correlation between water content parameters and leaf reflectance at 1,450, 1,650 and 2,250 nm, however, this correlation was not seen at 975 and 1,175 nm absorption bands. The study of Danson et al (1992) showed that when the leaf internal structure varies, the first derivative of leaf reflectance is superior to the original reflectance data for the estimation of leaf water content. It is believed that the variation in leaf structure causes the magnitude of leaf reflectance to change irrespective of the leaf water content.…”
Section: Research Articlementioning
confidence: 99%
See 2 more Smart Citations
“…Danson et al (1992) showed that the first derivatives of reflectance associated with the slopes of the lines near water-absorption bands were highly correlated with leaf water content. Gitelson et al (2003a) developed a technique based upon remote sensing that accounted for more than 90 percent of the variability in mid-day canopy photosynthesis of irrigated corn.…”
Section: Other Measurable Biophysical Variablesmentioning
confidence: 99%